Diagnosis and management of giant cell arteritis and polymyalgia rheumatica: challenges, controversies and practical tips. Issue 1051 (25th January 2013) - Mackie, Sarah Louise; Pease, Colin Thomas
Abstract : Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are inflammatory rheumatic diseases that may present to a variety of disciplines and specialities. The mainstay of treatment is glucocorticoids (steroids); together PMR and GCA now represent one of the most common reasons for medium-to-high dose, long-term glucocorticoid treatment in primary care. However, adverse effects of glucocorticoids are common in these patients. Management of both diseases involves balancing the symptoms and risks of the disease against the adverse effects and risks of glucocorticoids. The crucial first step in management is to make a firm, well-documented diagnosis, since once glucocorticoids are started they can mask the symptoms of a number of other diseases. Diagnosis however can be challenging and there are still substantial gaps in the evidence for treatment.